LY6E: a conductor of malignant tumor growth through modulation of the PTEN/PI3K/Akt/HIF-1 axis - Yeom, CJ; Zeng, L; Goto, Y; Morinibu, A; Zhu, Y; Shinomiya, K; Kobayashi, M; Itasaka, S; Yoshimura, M; Hur, C-G; Kakeya, H; Hammond, EM; et al. (Impact Journals, 2016)
Lymphocyte antigen 6 complex, locus E (LY6E) has been implicated in the malignant progression of various types of cancers; however, the underlying mechanism remains unclear. Here, we identified LY6E as an activator of HIF-1 and revealed their mechanistic and functional links in malignant tumor growth. The aberrant overexpression of LY6E increased HIF-1α gene expression principally at the transcription level. This, in turn, led to the expression of the pro-angiogenic factors, VEGFA and PDGFB, through decreases in the expression levels of PTEN mRNA and subsequent activation of the PI3K/Akt pathway. The LY6E-HIF-1 axis functioned to increase tumor blood vessel density and promoted tumor growth in immunodeficient mice. LY6E expression levels were significantly higher in human breast cancers than in normal breast tissues, and were strongly associated with the poor prognoses of various cancer patients. Our results characterized LY6E as a novel conductor of tumor growth through its modulation of the PTEN/PI3K/Akt/HIF-1 axis and demonstrated the validity of targeting this pathway for cancer therapy.